Influence of the conservation status on carbon balances of semiarid coastal Mediterranean wetlands. Issue 4 (1st October 2020) - Morant, Daniel; Picazo, Antonio; Rochera, Carlos; Santamans, Anna C.; Miralles-Lorenzo, Javier; Camacho, Antonio
ABSTRACT: Permanent freshwater and brackish marshes are the typical wetland type of the Mediterranean Spanish coast. Historically, alterations to the original morphological and hydrological characteristics of some these ecosystems have increased their trophic status, which could influence the carbon (C) balance, while other ecosystems remain close to their natural condition. In this work, the main processes related to the C cycle were studied in several Mediterranean coastal marshes with different degrees of alteration and in sites restored and managed in different ways. Carbon associated with greenhouse gases (CO2 and CH4 ) was determined using gas exchange methods for plankton, benthos, and sediments, as well as net production estimations for helophytes, to determine the influence of wetland conservation status, restoration, and management practices on C balances. Freshwater and brackish marshes showed capacity for C capture, especially in the restored sites (∼950  g m −2 yr −1 ), with a paramount role of helophytes. Differences among the study sites revealed the importance of alterations and restoration for C exchange. Specifically, a highly altered site showed increased rates of aerobic respiration compared to undisturbed sites, with a decrease in C storage capacity to ∼50  g m −2 yr −1 . Management practices resulting in instability of the organic sediments favoured degradative metabolism, with release of stored C and concomitant increases in CH4 emissions. Our results indicate that the hydromorphological alterations in these sites may convert healthy ecosystems contributing to C sequestration and climate change mitigation into C-emitting ecosystems.